Cost–benefits analysis in public law - A. V. Dolzhikov (Правоприменение, 2023)
The subject-matter of the research is economic analysis in public law. This method evaluates both costs and benefits of the regulatory measures. When assessing the alternatives, the judges in public litigation take into account their side effects. If an economically effective alternative is found, it should be ensured that it imposes a minimal burden on the rightholder or the costs to third parties.The purpose of the research is to argue that the cost-benefits analysis should be limited primarily to the economic field. Otherwise, personal, political, and social rights can be conferred with the properties of goods (commodification).The methodology of research is based on approaches of school “law and economics”. Economic analysis of law makes it possible to construct a scale of constitutional values, albeit not uncontroversial, but universal. This scale offers the important advantage of introducing proportionality for seemingly disparate individual freedoms and public interests. The introduction of material and financial scales, including compensation even for irreparable intangible goods, represents a better solution than the available alternatives.The main results of the research and the scope of their application. The above-mentioned method consists of assessing the costs and benefits both for the right-holders and for achieving the common good. It is necessary to analyse the costs and benefits of the challenged legal provision to individuals. Then, the governmental costs incurred in using alternative means should be reviewed. The public authorities should not incur excessive organisational or financial costs from a legal alternative that is humane to the individual. Due to the objective constraint on public resources, judges take into account future budgetary expenditures.In constitutional adjudication and administrative litigation, cost-benefit analysis is most effective in the economic sphere. It is easier to ensure the measurability of judicial review, usually in monetary or other material terms. The preparatory works, including the financial and economic justification of draft laws or regulations, may serve as an informational source in reviewing the legislative provisions and administrative acts which entail material costs. The cost-benefit analysis is applicable to non-material sphere. Although such costs generated by regulators are often difficult to assess in public law. A cost-benefit analysis is possible even in the political sphere. At the same time the judges usually restrain itself from assessing the political expediency of legislative decisions and administrative actions. Conclusions. There is a danger of economic analysis being abused in public law. The disadvantages of using this methodology include the possible devaluation of values which are essential for democracy. The abstract common good and reducing public expenditure will prevail over individual freedoms.